The truth about smoking - Kittleson, Mark J.; McCay, William (New York : Facts on File, 2005)
Provides facts and information for teens and young adults about issues related to smoking. Presented in an A to Z format accompanied by question and answer and fact versus legend segments.
7-A.
Includes bibliographical references and index.
Keywords: Smoking -- Health aspects; Tobacco habit -- Health aspects